2018
DOI: 10.1164/rccm.201706-1110oc
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Tumor-Infiltrating T Cells in Patients with Chronic Obstructive Pulmonary Disease Impact Lung Cancer Response to PD-1 Blockade

Abstract: COPD is associated with an increased sensitivity of CD8 tumor-infiltrating T lymphocytes to immune escape mechanisms developed by tumors, thus suggesting a higher sensitivity to PD-1 blockade in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 50 publications
8
90
1
Order By: Relevance
“…Most (53/59) of the patients with COPD in the present study were of mild to moderate severity, in accordance with previous studies . The subgroup analysis according to COPD severity revealed that those with mild COPD showed the greatest improvement in OS and PFS.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Most (53/59) of the patients with COPD in the present study were of mild to moderate severity, in accordance with previous studies . The subgroup analysis according to COPD severity revealed that those with mild COPD showed the greatest improvement in OS and PFS.…”
Section: Discussionsupporting
confidence: 90%
“…However, only 30% of these patients had documented spirometry and the COPD diagnoses were clinically determined. Another study, by Biton et al ., recapitulated this finding in 39 patients with NSCLC who received nivolumab . Although COPD was defined using post‐bronchodilator spirometry, given the small number of patients in that study, the statistical power may have been insufficient to determine the effect of nivolumab on OS.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations